Penyuluhan Dapatkan, Gunakan, Simpan, dan Buang (DAGUSIBU) Obat dengan Benar di Desa Kekeran Bali - Pande Made Desy Ratnasari; Kadek Duwi Cahyadi; Elizabeth Oriana Jawa La; Gede Arya Rizky Artana; Laili Kurnia Rizqy; Ni Kadek Mirah Rahayu (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
Currently, there is an increase in in the community, including the community in Kekeran Village. This must be balanced with good knowledge regarding how to administer drugs properly to avoid the impact of drug misuse. However, the survey results show that the community in Kekeran village have never received information related to drug management. This can affect the success of the community in carrying out self-medication. With these problems, we as the community service made efforts in the form of counselling activities to get, use, store, and dispose (DAGUSIBU) of drugs correctly which aims to increase the knowledge of the community of Kekeran Village regarding drug management. The method used in this counselling is the method of socialization in the form of presentations with the help of power points and booklets as well as the question and answer method with the intended target, namely housewives (IRT). Based on the socialization, the presence of participants met the target, namely the total number of IRTs totalling 28 people (100%) and most of them were active in the question and answer session (57.14%) which indicated the activity was enthusiastically welcomed by the community. The measurement of the knowledge level of IRT in Kekeran Village was carried out using pre-test and post-test questionnaires. From the results of the questionnaire, it was found that before the counselling, the knowledge of IRT regarding the DAGUSIBU was still low (42.14%). However, after the counselling was carried out, the knowledge of IRT in Kekeran village was classified as good (98.83%). Based on this, it can be concluded that there was an increase in public knowledge that previously did not or did not know to know about how to manage drugs properly (56.19%). Therefore, this activity should be routinely carried out in Kekeran Village so that the community to manage drugs